Morphologic characteristics of nevi associated with melanoma: a clinical, dermatoscopic and histopathologic analysis - Temeida Alendar; Harald Kittler (Mattioli1885, 2018)
Background: The aim of this retrospective study was to determine the frequency of nevus-associated melanomas and to better characterize the preexisting nevus from a histopathologic, clinical and dermatoscopic point of view. Methods: We reviewed the histopathologic slides of a consecutive series of 357 melanomas and corresponding clinical and dermatoscopic images, if available. Results: We found that 31 (8.7%) melanomas were associated with a preexisting nevus, 284 (79.5%) melanomas developed de novo, and in 42 (11.8%) a preexisting nevus could not be excluded, although the alternative explanation that the entire lesion represented a melanoma was also possible. The preexisting nevus was a "superficial" or "superficial and deep" congenital nevus in 27 cases (87%) and a Clark nevus in 4 cases (13%). Clinical or dermatoscopic images were available in 149 (41.7%) cases. The preexisting nevus, if visible, looked inconspicuous clinically or dermatoscopically. The median invasion thickness of nevus-associated melanoma was not significantly different from "de novo" melanomas but the frequency of in situ melanomas was higher in the "de novo" group (40.1% versus 16.1%). Patients with melanoma in association with a nevus were significantly younger (mean age=55 years, SD: 16 years) than patients with "de novo" melanomas (mean age=68 years SD: 15 years, p<0.001). When controlled for age and invasion thickness overall, survival did not differ significantly between patients with nevus-associated melanomas and patients with de novo melanomas. Conclusions: From a histomorphologic point of view, the majority of melanomas arise de novo. If melanomas develop in a preexisting nevus, they usually occur in association with a "superficial" or "superficial and deep" congenital nevus.